Fun algorithmic mathematics with IPMA influence as a basis for learning in Software Development - Tutillo Arcentales, Iván (2025)
Fun Algorithmic Mathematics is an educational project designed for problem-solving in the classroom, applied to core subjects in the Software Development program at ITB Technological Institute. It is analyzed from the perspective of the IPMA Project Management Model, which provides a useful software framework for project planning and management. This project focuses on the relevance of developing workshops in fundamental mathematics courses to foster a logical-algorithmic culture through solution modeling using propositional functions and common technological tools. This practical and functional educational awareness is based on respect for natural laws and the social norms of human logical behavior. Since all project management competencies are influenced to varying degrees by the logical-algorithmic culture acquired by project managers, the implementation of this approach is justified, with the IPMA Model serving as a resource for planning and execution. The project phases are defined as analysis, design, execution, and evaluation with feedback. The conclusions highlight the necessity of working with educators who have undertaken similar initiatives and the establishment of components that ensure the flexibility of workshops, allowing them to achieve their goal of developing a logical-algorithmic culture within the teaching and learning environment.